The Lutheran Confessional Writings for the 21st Century: A Question of Translation - Russell, William R. (Dialog, 2003)
The 21st century shift of the church's “center of gravity” from North America and Europe to Asia, Africa, and South America, provides a context in which translating the Lutheran confessional writings— and the theology to which they point—will play a vitally important role in the life of “...the one, holy, catholic, and apostolic church.”